The Effectiveness of PQ4R Strategy on the Development of Reading Comprehension Skills of the English Language Course among Second Intermediate Grade Students (Female Students) - Dakhiel, Maysoon Abdelazeez; Al sulami, Wazeera Farajallah (Journal of Educational and Psychological Sciences, 2021)
The current study aimed at investigating the effectiveness of PQ4R Strategy in developing reading comprehension skills of the English Language Course among second intermediate grade students. The study adopted a quasi-experimental design employing two groups (experimental and control). The design included an independent variable (PQ4R Strategy) and a dependent variable (reading comprehension skills). The sample of the study consisted of 2nd Intermediate Grade Students from schools in Al kamel (N=47). The students were divided into two groups experimental and control. The experimental group (N=23) was taught the reading comprehension texts of the super Goal 3 book through PQ4R Strategy. The control group (N=24) was taught the same texts through the traditional method. To achieve the goal of the research, a guide was prepared for the teacher to implement the strategy and reading comprehension test designed by the researcher. Results revealed that PQ4R Strategy had a positive effect on the students’ reading comprehension. In light of the study results, the researcher recommended the following: using PQ4R Strategy for developing reading comprehension skills of English language students’.